The Effect of Retinal Illuminance on the Subjective Amplitude of Accommodation. Issue 8 (August 2020) - Lara, Francisco; Del Águila-Carrasco, Antonio J.; Marín-Franch, Iván; Riquelme-Nicolás, Resurrección; López-Gil, Norberto
Abstract : SIGNIFICANCE: We show that the amplitude of accommodation decreases with retinal illumination even under photopic reading conditions and a constant pupil size. This result provides a basis for clinical approaches that are not based on an optical explanation. PURPOSE: We investigated the effect of retinal illuminance on the amplitude of accommodation while the pupil of the eye remained constant. METHODS: The amplitudes of accommodation of 10 young subjects (from 20 to 38 years of age) and that of 10 presbyopic subjects (from 45 to 54 years of age) were measured subjectively through an artificial pupil of 5 mm using a Badal optometer and for four values of retinal illuminance: 222, 821, 2138, and 5074 trolands. Phenylephrine was instilled to all the subjects to ensure that their natural pupil was greater than the artificial one in all experimental runs. Linear mixed-effects model for repeated measures with age and log luminance as covariates were used to check whether changes in amplitude of accommodation with retinal illumination were statistically significant. RESULTS: In the range of illuminances tested, the amplitude of accommodation decreased on average from 6.34 to 4.35 D in the young subjects and from 1.69 to 1.04 D in the presbyopic subjects. Illuminance was associated with the amplitude of accommodation in both young and presbyopic groups, with P < .01. CONCLUSIONS: The reduction in the amplitude of accommodation with target illumination (a phenomenon named night presbyopia ) under photopic light conditions is not only due to a reduction in the depth of focus as a consequence of pupil dilation; it is strongly affected by the decrease of retinal illumination.